Reporting specifications regarding epilepsy practice guidelines based on the RIGHT reporting checklist: an analysis - Yu Zhang; Wei Guo; Zhijie Wang; Xiaoyang Mio Hu; Xiao Gao (BMJ Open)
Objective Clinical guidelines are designed to optimise patient care and provide efficient approaches for therapy. Epilepsy is a chronic brain disorder that continues to experience a considerable treatment gap due to non-standard recommendations. We assessed the reporting quality of clinical practice guidelines on epilepsy over the past 5 years to generate a reporting specification for this study.Setting Seven databases were searched in May 2018 focusing on the period from 2013 to 2018. These included Medline, EMBASE, PubMed, Cumulative Index to Nursing and Allied Health Literature, China National Knowledge Infrastructure, Wanfang and Chinese Science and Technology Journal Database (VIP). Reporting quality of epilepsy guidelines was assessed by two independent authors using the Reporting Items for practice Guidelines in HealThcare (RIGHT) approach. Spearman’s correlation was used to assess inter-rater reliability.Participants Participants with epilepsy or seizure, not limited by age, gender, course of disease or cause of epilepsy, were included.Interventions There were no limitations with regard to intervention.Primary and secondary outcome measures The outcome was the ability of the RIGHT tool to measure reporting quality.Results Twelve relevant guidelines were included in this study. The reporting quality was not high in any of the included guidelines. The highest reporting quality included a ‘yes’ proportion of 77.1%, whereas the worst included a corresponding proportion of 37.1%. Overall evaluation results showed that 16.7% of the included guidelines were of high quality, 75% were of medium quality and 8.3% were of low quality. The correlation between the two estimators was credible (ρ>0.7).Conclusions Appraisal of these guidelines using the RIGHT tool revealed that the quality of reporting varied among guidelines. Items that exhibited low quality in most included guidelines were healthcare questions, rationale/explanation for recommendations, quality assurance, funding source(s) and role(s) of the funder, and limitations of the guideline. Thus, these aspects should receive greater attention in future guideline reporting.